13. Total Microbial Contamination Are Added To Meat Curry Leaf Extract (Murraya Koenigii) The Concentration And Old Storage Different - Rastina Rastina; Hanisah Hanisah; Rosmaidar Rosmaidar; Razali Razali; T. Armansyah TR; Sri Wahyuni (Jurnal Medika Veterinaria, 2019)
This research aim to study the effect of curry leavesaddition in extracts form with different concentration and storage time to the total microbes on fresh beef. This study use beef sample obtained from Lambaro Market Aceh Besar. The sample was divided into 36 sections, each wieght 25 grams and curry leaf extracts add with 0%, 25% and 50%concentrations, and were stored at 4-10oC. Microbiological examination of beef using pour plate method. Observations were made every 3 days in day 0, 3, 6 and 9. Measured parameters is total bacteria (CFU / gr). Data processing is using analysis of variance and the significantly different results tested with Duncan Test. Observation total of microbes on day 0 the concentration of 0% (without the addition of curry leaf extract), 25% and 50% was 2.7 x 102 CFU / gr, 2.2 x102 CFU / gr and 6.8 x101. It still can be consumed because it is still below the safety zone1x104 CFU / gr accordance with SNI 01-6366-2000 (SNI 2008). Meanwhile the observations at 0% concentration after 3 days already exceeded the standard of SNI 4.2 x106 cfu / gr. Meat with 50% curry leaf extract addition is still safe to eat up to day 9. Interaction effect between the concentration and the curry leaf extract addition and storage timeto the total microbe is not significantly different (P 0.01). Curry leaf extract addition and storage time factors is very significant (P 0.01) to the total microbes. These results indicated that curry leaf effective  into a preservative against fresh meat.